Religion in Southeast Asia: an encyclopedia of faiths and cultures - Athyal, Jesudas (ABC-CLIO, 2015)
"This engaging encyclopedia covers the religions and religious traditions of various Southeast Asian countries, including Brunei, Burma, Cambodia, Indonesia, Laos, Malaysia, the Philippines, Thailand, and Vietnam"--
Includes bibliographical references and index. - Print version record
Keywords: Southeast Asia -- Encyclopedias -- Religion -- Southeast Asia -- Encyclopedias; Electronic books; Wörterbuch; Religion; Südostasien